Nutritional Considerations of Cardiovascular Diseases and Treatments. (March 2019) - Boban, Marko; Bulj, Nikola; Kolačević Zeljković, Matea; Radeljić, Vjekoslav; Krcmar, Tomislav; Trbusic, Matias; Delić-Brkljačić, Diana; Alebic, Tamara; Vcev, Aleksandar
Nutritional considerations of many chronic diseases are not fully understood or taken into consideration in everyday clinical practice. Therefore, it is not surprising that high proportion of hospitalized patients with cardiovascular diseases remains underdiagnosed with malnutrition. Malnourished patients have increased risk of poor clinical outcomes, complications rate, prolonged hospital stay, more frequent rehospitalizations, and lower quality of life. The purpose of this review is to recapitulate recent data on nutritional considerations in cardiovascular medicine.